2021
DOI: 10.1002/er.7425
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance cost minimization models for offshore wind farms: A systematic and critical review

Abstract: Feasible and sustainable source of power is a burning question nowadays. The offshore wind farms can be a solution to power generation problem, but it is relatively more expensive. Its installation cost is more than twice of its similar size onshore counterpart. The cost that matters most is the operations and maintenance (O&M) cost. Expensive and sophisticated transfer vehicles as well as highly skilled technicians are needed to conduct O&M activities, which results in a remarkably higher O&M cost for an offs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 185 publications
(161 reference statements)
0
12
0
Order By: Relevance
“…Investment incentives: People are desperately looking for sustainable forms of energy (Tusar and Sarker, 2020). Nowadays, there are plenty of incentives offered for the promotion of renewable energy in terms of tax, grants and other credits.…”
Section: Site Selection For Owfmentioning
confidence: 99%
See 1 more Smart Citation
“…Investment incentives: People are desperately looking for sustainable forms of energy (Tusar and Sarker, 2020). Nowadays, there are plenty of incentives offered for the promotion of renewable energy in terms of tax, grants and other credits.…”
Section: Site Selection For Owfmentioning
confidence: 99%
“…Operation and maintenance cost: The maintenance of offshore wind farms is highly dependent on the weather conditions (Tusar and Sarker, 2022a). It is difficult to access the turbines during rough and hostile weather conditions.…”
Section: Owf Development Stagesmentioning
confidence: 99%
“…Ro¨ckmann et al (2017) and Meng et al (2016) reported that operations and maintenance cost is 1/5th of the total life cycle cost of OWF. The primary goal of maintenance is to reduce downtime (Tusar and Sarker, 2022). Van Horenbeek and Pintelon (2013) showed that assigning a penalty cost in the inventory model can take care of this issue.…”
Section: Current State Of Spare Parts Researchmentioning
confidence: 99%
“…Compared to fossil fuel technologies, renewable energy resources need experienced employees to install several types of solar panels. Wind farms also need technicians and maintenance teams to manage proper strategy of work [11]. More job opportunities are enhanced with help of these renewable energy resources.…”
Section: Figure 1: Net Capacity Additions Of Renewable Energymentioning
confidence: 99%